المنهج القرآني في الحذر وتوقي الضرر : دراسة تحليلية لحوارات من القرآن الكريم - شعبني، مبارك بن مسلم (al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This research has been conducted to find out the method of awareness and avoiding harm. And that is through the study of Qur’ānic dialogues in which it is remarked and clarified. As it is intended to conclude the educational evidences and the content which carries the remarked awareness. In fact I have conducted this study to follow up the Qur’ānic dialogues which includes awareness from harm and then avoidance, and then I have changed those dialogues by studying and analyzing. This study contains four chapters and the conclusion. The first chapter discusses the definition and basics of the study and clarifies the point that there is a clash between awareness and avoiding harm and the destiny which is from Allah (SWT). The second chapter includes some Qur’ānic dialogues which are about awareness and avoiding harm, which resulting disobedience to Allah (SWT). The third chapter discusses the Qur’ānic dialogues in which there are awareness and avoiding harm from an Individual. The fourth chapter discusses a group of Qur’ānic dialogues in which there are awareness and avoiding harm from a society or nation. The conclusion discusses the summary of the methodology. Indeed the methodology which being used is inductive, analytical and deductive. The end result of the study showed that the Qur’ānic methodology in awareness and avoiding harm representing the need of inductive reasons of safety, security and the inductive reasons of harm, disaster and how to avoid from them. There are several ways for summarizing the Qur’ānic methodology which representing the obedience to Allah (SWT) and those are obedience to His commands and avoid for what He forbidden. To rely on Allah and to submit the overall affairs to Him, to ask for His help, to take the responsibility of preaching people to His true path, to enjoin the good and to forbid from bad, to be patient, to bear the hardships for the sake of good and benefit, to vision the up coming planning and consulting, to consider the audience and to cover them for what they supposed to be covered. To invigilate the harmful techniques, to be far way from harmful and dangerous places, to be aware and curious, and to get ready to face any unexpected harm.